Sistem Pakar Pemilihan Menu Makanan Bergizi untuk Anak Balita Menggunakan Metode Certainty Factor Berbasis Web - Maria Fransiska Sare Labina; Diah Arifah Prastiningtyas (LPPM STIKI MALANG, 2020)
Food is a primary need for humans, because food is a source of energy needed by humans. The type of food itself is very varied, such as food in soup, fried foods, and others. Selection of the food menu itself is also very important, because apart from being a source of energy needed by humans, food can also help maintain the health of the human body, therefore choosing a food menu that is careless or does not have sufficient nutritional content is not recommended by doctors or experts. nutrition. Foods that are categorized as nutritious must have a balanced composition in terms of cooking ingredients, such as vegetables, side dishes and other processing ingredients. This nutritious food menu is not limited to children, adolescents, or adults only, but also for toddlers (under five years old), because at the age of a toddler, nutritious food is needed to help the growth and development of his immune system. That parents who have toddlers are strongly encouraged to choose a good food menu for their children.